The Pressure on Higher Education Performance and the Process of Lifelong Learning - Alka Obadić; Anna-Marija Jakšić (Central European Public Administration Review)
Knowledge has become the central resource in the economy of the "information" or "post-industrial" society. Therefore, analysis in the article elaborates European higher education system and the relationship between educational attainment and the employment rate in EU countries and their position in world leading markets. Enclosed, the study analyses the progress and current trends of lifelong learning (LLL) performance in EU and Croatia. The research analyses five EU benchmarks for education and training system set by the European Council, and their implications’ on labour market performance. Some synthesis of previous studies is also used. The methodological approach uses the worldwide UN Education Index, the European Commission data on higher education, Eurostat LFS data, and Cedefop data of Vocational Training.